Implementation of the Use of Co-Branding of Yogyakarta Specialty Products and Dispute Resolution of Trademark Infringement Rights - Ekasari, Rellyta Dea; Mudiparwanto, Wahyu Adi (LEGAL BRIEF, 2024)
Micro, small, and medium enterprises (MSMEs) are one way the government can achieve maximum economic growth. The number of established MSMEs has resulted in the emergence of many new brands, increasing the opportunity for violations. Therefore, public awareness and the role of local government in protecting MSMEs in the region are needed . In addition to adhering to the Trademark Law, the Special Region of Yogyakarta initiated an innovative regulation governing Co-Branding Jogja to protect the essence of intellectual property rights owned by MSMEs, especially trademark rights. This research uses a normative-empirical type of legal research with qualitative data analysis. The results of this study show that there are still obstacles to implementing the use of the Jogja co-branding brand. However, the government seeks to continue evaluating regulations to solve these problems. Regarding alternative dispute resolution, the government cooperates with the Regional Office of the Ministry of Law and Human Rights of Yogyakarta by facilitating complaints if the Trademark Rights holders find their trademarks used by others without permission